PRAKTIK PINJAMAN DARI BANK KELILING DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DITINJAU DARI HUKUM ISLAM - Arif Fahrudhin; Irvan Iswandi; Ahmad Asrof Fitri (Melati Institute, 2023)
In everyday life, people often need lenders for urgent needs or additional capital in order for their businesses to be able to continue. Apart from official financial institutions, there are also mobile banks in the community which have their own existence because they provide convenience on terms and conditions in lending to the community, but have higher interest in return. The purpose of this research was to find out the practice of mobile bank loans in increasing people's income in Sub-village of Sembung I and to find out the review of Islamic Law on the practice of mobile bank loans in Sub-village of Sembung I. In this research, the authors used a qualitative research approach. In collecting data from the field, both from sources and in the form of documents related to the author using observation techniques, interviews and documentation. While the data processing and analysis techniques used by the authors are descriptive analysis and then interpreted in the form of qualitative descriptive. The results of this research showed that: First, Loans from Mobile Banks in increasing people's income in Sub-village of Sembung I, turned out not to be able to significantly increase people's income. Second, According to Islamic law, the existence of mobile banks whose purpose is to increase people's income is unlawful according to Islamic law. Because it contains elements of usury in it and in practice mobile banks bring more harm than benefits.